Mapping Relation of Leakage Currents of Polluted Insulators and Discharge Arc Area - Fang, Chunhua; Tao, Yuning; Wang, Jianguo; Ding, Can; Huang, Li; Zhou, Mi; Gu, Yi; Wang, Yali (Frontiers in Energy Research, 2021)
A fundamental parameter of polluted insulator online monitoring is the leakage current, which has already been shown to be well-related to the pollution discharge of insulators. In this article, in an effort to quantitatively reflect the discharge intensity and the discharge status by the leakage current, we carried out an experimental study on artificial pollution discharge of insulators. A high-speed photographic apparatus was utilized to capture the entire process of local arcs on a porcelain insulator surface, including the arc generation, the arc development, and the flashover, for which the associated leakage current of insulators was synchronously digitized. A comparative analysis of the relation between the two-dimensional discharge image and the leakage current waveform in the process of arc generation and development shows that if the arc area on the insulator surface is relatively small and the leakage current passes through zero, the arc might completely become extinct, whereas this phenomena will not occur if the arc area is larger. In addition, the amplitude of the discharge arc area is found to be roughly proportional to the square of leakage current over the range of leakage current amplitude from 0 to 150 mA. Our results can provide an important guidance for judgment of the discharge status and the discharge intensity on insulator surfaces using the leakage current of insulators.